Cobalt-nickel oxide doped graphene aerogel composite material as well as preparation method and application thereof

By using cobalt-nickel oxide doped graphene aerogel composite material as a gas-sensitive material, the problems of long response time, high operating temperature and poor selectivity of existing gas sensors are solved, and high sensitivity and selectivity detection of H2 are achieved , has good repeatability and gas-sensitive performance, and is suitable for thermal runaway monitoring and early warning of lithium batteries.

CN119490237APending Publication Date: 2025-02-21CHN ENERGY NEW ENERGY TECHNOLOGY RESEARCH INSTITUTE CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411610336.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

Existing gas sensors have problems such as long response/recovery time, high operating temperature and poor selectivity, which are difficult to meet the increasingly stringent performance requirements, especially in the monitoring and early warning of thermal runaway for lithium batteries.

Method used

Cobalt-nickel oxide-doped graphene aerogel composite material, which has a porous nanoflower structure, is prepared by solvent heat treatment and calcination, has a large specific surface area and many active sites, as a gas-sensitive material at a lower working temperature It has high sensitivity and high selectivity for H2.

Benefits of technology

It has achieved high sensitivity and high selectivity to H2 at a lower working temperature, good repeatability and gas sensitivity, and can detect gas discharged from thermal runaway lithium batteries in a timely manner and make early warnings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490237A_ABST
    Figure CN119490237A_ABST
Patent Text Reader

Abstract

The invention relates to the field of sensor materials, and discloses a cobalt-nickel oxide doped graphene aerogel composite material as well as a preparation method and application thereof. The cobalt-nickel oxide doped graphene aerogel composite material is in a porous nanoflower shape, has a large specific surface area and more surface active sites, combines the advantages of a metal oxide semiconductor and graphene, and is beneficial to improving the gas-sensitive property. The preparation method of the cobalt-nickel oxide doped graphene aerogel composite material comprises the following steps: mixing cobalt salt, nickel salt, graphene and other raw materials, and then sequentially carrying out solvent heat treatment, freeze drying and calcination, so that a nano flower-shaped structure can be well maintained, and a large specific surface area can be maintained. When the aerogel composite material is used as a gas-sensitive material, the aerogel composite material shows high sensitivity and high selectivity to H2, and is beneficial to early warning of thermal runaway of the lithium battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of sensor materials, and specifically to a cobalt-nickel oxide-doped graphene aerogel composite material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries (LIBs) are highly favored for their high energy density and long cycle life, but their safety issues have always been a key factor limiting their use. Studies have shown that the direct cause of accidents in energy storage power stations or electric vehicles is mostly thermal runaway of a certain part of the lithium battery, and the thermal runaway process is often accompanied by a large number of side reactions and the release of gases, among which the main gas types include hydrogen, carbon dioxide, methane, carbon monoxide and ethylene. When thermal runaway develops to a certain stage, the concentration of gases such as H2, CO2, CH4, C2H4, and CO has increased significantly before entering the smoke stage, especially the detection of H2 is more advanced than the detection of other thermal runaway characteristic gases. Therefore, the use of gas sensors to detect batteries in real time can realize early battery fault detection and avoid disasters.

[0003] At present, in the field of gas sensors, semiconductor metal oxide nanosheets have attracted widespread attention due to their high specific surface area and specific crystal interface exposure, which have good sensing performance. However, gas sensors made of single metal oxide semiconductor materials have disadvantages such as long response / recovery time, high operating temperature and poor selectivity, which cannot meet the increasingly stringent performance requirements, and seriously limit the further application of semiconductor sensors. Especially for the monitoring and early warning of thermal runaway of lithium batteries, gas sensors with fast response and recovery, low operating temperature and high selectivity are more needed. Summary of the invention

[0004] The purpose of the present invention is to overcome the problems of long response / recovery time, high operating temperature and poor selectivity in the prior art, and to provide a cobalt-nickel oxide-doped graphene aerogel composite material and a preparation method and application thereof. The cobalt-nickel oxide-doped graphene aerogel composite material presents a porous nanoflower structure, has a large specific surface area and more active sites; when the material is used as a gas-sensitive material, it has high sensitivity and high selectivity to H2 at a relatively low operating temperature (such as 120°C) and good repetitive stability; the material can be prepared by simple solvent thermal treatment and calcination, and the method is simple and efficient.

[0005] On the one hand, the present invention provides a cobalt-nickel oxide-doped graphene aerogel composite material, which contains cobalt oxide, nickel oxide and reduced graphene oxide, and is in the shape of porous nanoflowers with a specific surface area of ​​80-100 m 2 / g.

[0006] Preferably, in the cobalt-nickel oxide-doped graphene aerogel composite material, relative to 100 parts by weight of the reduced graphene oxide, the content of the cobalt oxide is 25-50 parts by weight, and the content of the nickel oxide is 5-35 parts by weight.

[0007] Preferably, the cobalt oxide is Co3O4, and the nickel oxide is NiO.

[0008] A second aspect of the present invention provides a method for preparing a cobalt-nickel oxide-doped graphene aerogel composite material, comprising the following steps: (1) mixing an alcohol solution of cobalt salt and nickel salt, an aqueous solution of hexamethylenetetramine, and a mixed solution containing graphene oxide and N,N-dimethylformamide, and then performing a solvent thermal treatment to obtain a hydrogel; (2) freeze-drying the hydrogel obtained in step (1), and calcining the obtained aerogel.

[0009] Preferably, in the alcohol solution of the cobalt salt and the nickel salt, the concentration of the cobalt salt is 0.04-0.50 mol / L, and the concentration of the nickel salt is 0.02-0.20 mol / L.

[0010] Preferably, the cobalt salt is cobalt nitrate and / or cobalt chloride, and the nickel salt is at least one of nickel nitrate, nickel chloride or nickel sulfate.

[0011] Preferably, in the hexamethylenetetramine aqueous solution, the concentration of hexamethylenetetramine is 0.2-0.6 mol / L.

[0012] Preferably, in the mixed solution of graphene oxide and N,N-dimethylformamide, the concentration of graphene oxide is 5-15 mg / mL, and the volume fraction of N,N-dimethylformamide is 50-75 vol%.

[0013] Preferably, the solvent thermal treatment conditions include: temperature of 80-200° C. and time of 5-20 h.

[0014] Preferably, the freeze-drying conditions include: a temperature of -80°C to -55°C and a time of 18-36 hours.

[0015] Preferably, the calcination conditions include: temperature of 400-600° C. and time of 1-6 h.

[0016] The third aspect of the present invention provides a cobalt-nickel oxide-doped graphene aerogel composite material prepared by the aforementioned preparation method.

[0017] A fourth aspect of the present invention provides the use of the aforementioned cobalt nickel oxide doped graphene aerogel composite material as a gas sensitive material for a gas sensor.

[0018] A fifth aspect of the present invention provides a gas sensor, the gas sensitive material of which is the aforementioned cobalt nickel oxide-doped graphene aerogel composite material.

[0019] The cobalt-nickel oxide-doped graphene aerogel composite material of the present invention has a porous nano-flower-like microstructure, and therefore has a large specific surface area and a large number of active sites, and combines the advantages of both metal oxide semiconductors and graphene materials, so that the composite material has higher gas-sensing performance, better selectivity and repeated stability; a sensor prepared with the material as a gas-sensitive material responds to a variety of gases generated by thermal runaway of a lithium battery at a relatively low operating temperature, and in particular has high sensitivity (up to 93.6%) and high selectivity to H2, which is beneficial to early warning of thermal runaway of the lithium battery when in use, and the performance of multiple repeated tests is similar, with good repeatability.

[0020] According to the preparation method of the present invention, the cobalt-nickel oxide-doped graphene aerogel composite material can be prepared by simple solvent thermal treatment and calcination. The preparation process is simple, and freeze-drying and calcination can maintain the aerogel composite material in a porous nanoflower shape, so that the obtained aerogel composite material has a large specific surface area and more active sites, and has better gas-sensing performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 1 is a scanning electron microscope (SEM) image of the sensor material prepared in Example 1, (a) is the material before heat treatment, and (b) is the material after heat treatment at 500° C. in air; Figure 2 is a resistance response diagram of the sensor prepared in Example 1 to 10-5000 ppm H2 gas at a temperature of 120°C; Figure 3 is a resistance response diagram of the sensor prepared in Example 1 to 10-5000 ppm CH4 gas at a temperature of 120°C; Figure 4 is a resistance response diagram of the sensor prepared in Example 1 to 10-5000 ppm CO2 gas at a temperature of 120°C; Figure 5 is a sensitivity performance response diagram of the sensor prepared in Example 1 to 10-5000 ppm H2 gas at a temperature of 120°C; Figure 6 This is a comparison chart of the sensitivity of the sensor prepared in Example 1 to 200 ppm of H2, CH4, and CO2 gases at a temperature of 120°C; Figure 7This is the resistance response diagram of the sensor prepared in Example 1 repeatedly tested at 120°C for 100 ppm H2 gas. DETAILED DESCRIPTION

[0022] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0023] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0024] The cobalt-nickel oxide-doped graphene aerogel composite material of the present invention contains cobalt oxide, nickel oxide and reduced graphene oxide, and is in the shape of porous nanoflowers with a specific surface area of ​​80-100 m 2 / g. Preferably, the specific surface area is 85-100m 2 / g, more preferably 90-98m 2 In the present invention, the composite material having the above-mentioned morphology structure and specific surface area is selected to increase the exposure of active sites on the surface of the material, which is beneficial to the improvement of gas sensing performance.

[0025] In the aerogel composite material described in the present invention, preferably, relative to 100 parts by weight of the reduced graphene oxide, the content of the cobalt oxide is 25-50 parts by weight, and the content of the nickel oxide is 5-35 parts by weight. More preferably, relative to 100 parts by weight of the reduced graphene oxide, the content of the cobalt oxide is 30-45 parts by weight, and the content of the nickel oxide is 10-30 parts by weight. Most preferably, relative to 100 parts by weight of the reduced graphene oxide, the content of the cobalt oxide is 35-45 parts by weight, and the content of the nickel oxide is 15-25 parts by weight. In the present invention, selecting the composition ratio within the above range can ensure that the aerogel composite material has high sensitivity and high selectivity for H2 recognition, and maintains a porous nanoflower shape after calcination.

[0026] In the aerogel composite material of the present invention, preferably, the cobalt oxide is Co3O4 and the nickel oxide is NiO.

[0027] The cobalt-nickel oxide-doped graphene aerogel composite material of the present invention has a porous nanoflower-like microstructure and thus has a large specific surface area and a large number of active sites. It also combines the gas recognition capabilities of two metal oxide semiconductors with the advantages of high conductivity, high aspect ratio, large specific surface area and high stability of graphene materials, so that the composite material has higher gas-sensing performance, better selectivity and repeated stability.

[0028] The method for preparing the cobalt-nickel oxide-doped graphene aerogel composite material of the present invention comprises the following steps: (1) mixing an alcohol solution of cobalt salt and nickel salt, an aqueous solution of hexamethylenetetramine, and a mixed solution containing graphene oxide and N,N-dimethylformamide, and then performing a solvent thermal treatment to obtain a hydrogel; (2) freeze-drying the hydrogel obtained in step (1), and calcining the obtained aerogel.

[0029] In the method described in the present invention, preferably, in the alcohol solution of the cobalt salt and the nickel salt, the concentration of the cobalt salt is 0.04-0.50 mol / L, and the concentration of the nickel salt is 0.02-0.20 mol / L. More preferably, the concentration of the cobalt salt is 0.10-0.40 mol / L, and the concentration of the nickel salt is 0.08-0.16 mol / L. Most preferably, the concentration of the cobalt salt is 0.16-0.30 mol / L, and the concentration of the nickel salt is 0.08-0.12 mol / L. In the present invention, the above-mentioned concentrations of the cobalt salt and the nickel salt are used to ensure that the contents of cobalt oxide and nickel oxide in the final aerogel composite material are within a suitable range to obtain better gas-sensing performance.

[0030] In the method of the present invention, preferably, the cobalt salt is cobalt nitrate and / or cobalt chloride, more preferably cobalt nitrate. In some embodiments, the cobalt nitrate is used in the form of cobalt nitrate hexahydrate.

[0031] In the method of the present invention, preferably, the nickel salt is at least one of nickel nitrate, nickel chloride or nickel sulfate, more preferably nickel nitrate. In some embodiments, the nickel nitrate is used in the form of nickel nitrate hexahydrate.

[0032] In the method of the present invention, preferably, the concentration of hexamethylenetetramine in the hexamethylenetetramine aqueous solution is 0.2-0.6 mol / L, more preferably 0.3-0.5 mol / L, most preferably 0.35-0.45 mol / L.

[0033] In the method of the present invention, preferably, in the mixed solution of graphene oxide and N,N-dimethylformamide, the concentration of graphene oxide is 5-15 mg / mL, and the volume fraction of N,N-dimethylformamide is 50-75 vol%. More preferably, the concentration of graphene oxide is 1.2-2.8 mg / mL, and the volume fraction of N,N-dimethylformamide is 55-70 vol%. Most preferably, the concentration of graphene oxide is 1.5-2.5 mg / mL, and the volume fraction of N,N-dimethylformamide is 60-68 vol%.

[0034] In the method of the present invention, preferably, in step (1), in the suspension obtained by mixing the alcohol solution of the cobalt salt and the nickel salt, the aqueous solution of hexamethylenetetramine, and the mixed solution containing graphene oxide and N,N-dimethylformamide, the content of graphene oxide is 1-3 mg / mL, the concentration of the cobalt salt is 0.02-0.25 mol / L in terms of cobalt element, and the concentration of the nickel salt is 0.01-0.10 mol / L in terms of nickel element. More preferably, the content of graphene oxide is 1.5-2.5 mg / mL, the concentration of the cobalt salt is 0.05-0.20 mol / L in terms of cobalt element, and the concentration of the nickel salt is 0.02-0.08 mol / L in terms of nickel element. Most preferably, the content of graphene oxide is 1.8-2.3 mg / mL, the concentration of cobalt salt is 0.08-0.15 mol / L in terms of cobalt element, and the concentration of nickel salt is 0.03-0.06 mol / L in terms of nickel element.

[0035] In the method described in the present invention, preferably, the conditions of the solvent thermal treatment include: a temperature of 80-200°C and a time of 5-20h. More preferably, the temperature is 80-150°C and the time is 8-15h. Most preferably, the temperature is 80-105°C and the time is 9-12h. In the present invention, the above-mentioned solvent thermal treatment conditions can be used to form a cobalt nickelate / reduced graphene oxide (CoNiO2 / rGO) hydrogel, and it has a nanoflower-like morphology structure assembled from nanosheets, which is beneficial for the final product aerogel composite material to have a higher specific surface area and more exposed active sites, thereby obtaining better gas-sensing properties.

[0036] In the method of the present invention, preferably, the freeze-drying conditions include: a temperature of -80°C to -55°C and a time of 18-36 hours. More preferably, the temperature is -70°C to -60°C and the time is 20-28 hours. In the present invention, the freeze-drying conditions described above can maintain the original nanoflower-like structure substantially unchanged while the hydrogel is fully dehydrated to form an aerogel, which is conducive to maintaining a high specific surface area.

[0037] In the method described in the present invention, preferably, the calcination conditions include: a temperature of 400-600°C and a time of 1-6h. More preferably, the temperature is 450-550°C and the time is 2-5h. Most preferably, the temperature is 475-525°C and the time is 2.5-4h. In the present invention, the above-mentioned calcination conditions are adopted to ensure that the CoNiO2 in the CoNiO2 / rGO aerogel is converted into the corresponding cobalt nickel oxide, while maintaining the nanoflower structure before and after calcination basically unchanged, and forming a porous structure, which is conducive to the final aerogel composite material having a higher specific surface area and more exposed active sites, thereby obtaining better gas-sensing properties.

[0038] In a specific embodiment, the specific process of the preparation method may include: (1) adding a cobalt salt containing 1.6-20 mmol of cobalt element and a nickel salt containing 0.8-8 mmol to 40 mL of ethanol and stirring evenly to obtain an alcohol solution of cobalt salt and nickel salt (wherein the concentration of cobalt salt is 0.04-0.50 mol / L, and the concentration of nickel salt is 0.02-0.20 mol / L), wherein the cobalt salt is cobalt nitrate and / or cobalt chloride, and the nickel salt is at least one of nickel nitrate, nickel chloride or nickel sulfate; (2) Dissolve 4.8-14.4 mmol of hexamethylenetetramine in 24 mL of deionized water and stir evenly to obtain an aqueous solution of hexamethylenetetramine with a concentration of 0.2-0.6 mol / L; (3) Mixing the aqueous solution of graphene oxide with N,N-dimethylformamide and fully dispersing to obtain 16 mL of a mixed solution containing graphene oxide and N,N-dimethylformamide, wherein the concentration of graphene oxide in the obtained mixed solution is 5-15 mg / mL, and the volume fraction of the N,N-dimethylformamide is 50-75 vol%; (4) the alcohol solution, aqueous solution and dispersion obtained in steps (1), (2) and (3) are fully mixed, and then the obtained mixed solution is subjected to solvent thermal treatment to obtain CoNiO2 / rGO hydrogel, wherein the solvent thermal treatment conditions are: temperature of 80-200°C and time of 5-20h; (5) washing and soaking the CoNiO2 / rGO hydrogel obtained after the solvent thermal treatment in step (4) for multiple times to remove impurities, and then freeze-drying to obtain CoNiO2 / rGO aerogel, wherein the freeze-drying conditions are: temperature of -80°C to -55°C, and time of 18-36 hours; (6) The CoNiO2 / rGO aerogel obtained by freeze-drying in step (5) is calcined at 400-600°C for 1-6h to obtain a cobalt nickel oxide-doped graphene aerogel composite material (Co3O4 / NiO / rGO).

[0039] The preparation method of the cobalt-nickel oxide-doped graphene aerogel composite material of the present invention can obtain a hydrogel with a nanoflower-like morphology by a simple solvent thermal method, and then prepare an aerogel by freeze-drying, while maintaining the original microscopic morphology structure unchanged, and then control appropriate calcination conditions to obtain a porous nanoflower-like cobalt-nickel oxide / reduced graphene oxide aerogel. The method is simple and efficient.

[0040] Application of the aforementioned cobalt-nickel oxide-doped graphene aerogel composite material of the present invention as a gas-sensitive material of a gas sensor. When the cobalt-nickel oxide-doped graphene aerogel composite material of the present invention is used as a gas-sensitive material, a gas sensor having high sensitivity (93.6%) and selectivity to H2, low operating temperature (120°C) and good repetitive stability can be obtained, which is conducive to timely detection of the gas released by thermal runaway of the lithium battery and earlier warning.

[0041] In the application of the present invention, preferably, the following steps are included: S1. The commercially available flat-plate Au electrode (with extended platinum wire) was cleaned and dried with deionized water and ethanol respectively. The electrode was provided with a test electrode and a heating electrode. The electrode heating temperature could be controlled by adjusting the input current. The upper surface of the electrode was Au, which was the test end, and the lower surface was Ru, which was the heating end. The overall dimensions of the flat-plate electrode were 1.5×1.5 mm. S2. Weigh a certain amount of the cobalt-nickel oxide-doped graphene aerogel composite material of the present invention as a gas-sensitive material, add deionized water so that the mass ratio of deionized water to the gas-sensitive material is 1:1, and then quickly grind for 5-10 minutes to form a uniform paste slurry; S3. The slurry obtained in step S2 is evenly applied on the flat Au electrode to form an electrode film and completely cover the Au electrode. The obtained electrode is then placed on an aging table and aged at 60° C. for 48 hours.

[0042] The gas sensor of the present invention has a gas-sensitive material of the aforementioned cobalt-nickel oxide-doped graphene aerogel composite material. The gas sensor has a high sensitivity (93.6%) and selectivity to H2 at a relatively low operating temperature (120°C), which is conducive to timely detection of the gas released by thermal runaway of lithium batteries and earlier warning.

[0043] In the gas sensor of the present invention, preferably, it comprises a gas sensitive electrode coated by the method of the above steps S1-S3.

[0044] The following examples further illustrate the polyaniline derivatives and their preparation methods and applications of the present invention. The examples are implemented based on the technical solution of the present invention, and provide detailed implementation methods and specific operation processes, but the protection scope of the present invention is not limited to the following examples.

[0045] The experimental methods in the following examples, unless otherwise specified, are all conventional methods in the art. The experimental materials used in the following examples, unless otherwise specified, are all commercially available.

[0046] Example 1 (1) Add 8 mmol of cobalt nitrate hexahydrate and 4 mmol of nickel nitrate hexahydrate into 40 mL of ethanol and stir evenly until the mixture is completely dissolved to obtain an alcohol solution of cobalt salt and nickel salt; (2) Dissolve 10 mol of hexamethylenetetramine in 24 mL of deionized water and stir evenly to obtain an aqueous solution of hexamethylenetetramine; (3) 5.33 mL of a 10 mg / mL aqueous solution of graphene oxide was mixed with 10.67 mL of N,N-dimethylformamide, and ultrasonically stirred for 24 h to obtain a mixed solution containing graphene oxide and N,N-dimethylformamide after full dispersion; (4) the three solutions obtained in steps (1), (2) and (3) are fully mixed, and then the obtained mixed solution is transferred to a polytetrafluoroethylene-lined container, and subjected to solvent thermal treatment at 150° C. for 10 h to obtain a CoNiO2 / rGO hydrogel; (5) washing and soaking the CoNiO2 / rGO hydrogel obtained in step (4) for multiple times to remove impurities, and then freeze-drying at a temperature of -65°C for 24 hours to obtain CoNiO2 / rGO aerogel; (6) The CoNiO2 / rGO aerogel obtained in step (5) was calcined at 500°C for 3h to obtain the cobalt nickel oxide-doped graphene aerogel composite material of the present invention, which was recorded as CNG-1.

[0047] Example 2 (1) Add 4 mmol of cobalt nitrate hexahydrate and 2 mmol of nickel nitrate hexahydrate into 40 mL of ethanol and stir evenly until the mixture is completely dissolved to obtain an alcohol solution of cobalt salt and nickel salt; (2) Dissolve 5 mol of hexamethylenetetramine in 24 mL of deionized water and stir evenly to obtain an aqueous solution of hexamethylenetetramine; (3) 5.33 mL of a 5 mg / mL aqueous solution of graphene oxide was mixed with 10.67 mL of N,N-dimethylformamide, and ultrasonically stirred for 24 h to obtain a mixed solution containing graphene oxide and N,N-dimethylformamide after sufficient dispersion; (4) The three solutions obtained in steps (1), (2) and (3) are fully mixed, and then the obtained mixed solution is transferred to a polytetrafluoroethylene-lined container and subjected to solvent thermal treatment at 150° C. for 12 h to obtain a CoNiO2 / rGO hydrogel; (5) washing and soaking the CoNiO2 / rGO hydrogel obtained in step (4) for multiple times to remove impurities, and then freeze-drying at a temperature of -75°C for 20 hours to obtain CoNiO2 / rGO aerogel; (6) The CoNiO2 / rGO aerogel obtained in step (5) was calcined at 550°C for 2h to obtain the cobalt nickel oxide-doped graphene aerogel composite material of the present invention, which was recorded as CNG-2.

[0048] Example 3 (1) Add 18 mmol of cobalt nitrate hexahydrate and 8 mmol of nickel nitrate hexahydrate into 40 mL of ethanol and stir evenly until the mixture is completely dissolved to obtain an alcohol solution of cobalt salt and nickel salt; (2) Dissolve 14 mol of hexamethylenetetramine in 24 mL of deionized water and stir evenly to obtain an aqueous solution of hexamethylenetetramine; (3) Mix 5.33 mL of a 15 mg / mL aqueous solution of graphene oxide with 10.67 mL of N,N-dimethylformamide, and stir ultrasonically for 24 h to obtain a mixed solution containing graphene oxide and N,N-dimethylformamide after sufficient dispersion; (4) The three solutions obtained in steps (1), (2) and (3) are fully mixed, and then the obtained mixed solution is transferred to a polytetrafluoroethylene-lined container and subjected to solvent thermal treatment at 150° C. for 8 h to obtain a CoNiO2 / rGO hydrogel; (5) washing and soaking the CoNiO2 / rGO hydrogel obtained in step (4) for multiple times to remove impurities, and then freeze-drying at a temperature of -70°C for 30 hours to obtain CoNiO2 / rGO aerogel; (6) The CoNiO2 / rGO aerogel obtained in step (5) was calcined at 450°C for 5 hours to obtain the cobalt nickel oxide-doped graphene aerogel composite material of the present invention, which was recorded as CNG-3.

[0049] Example 4 (1) Add 8 mmol of cobalt nitrate hexahydrate and 2 mmol of nickel nitrate hexahydrate into 40 mL of ethanol and stir evenly until the mixture is completely dissolved to obtain an alcohol solution of cobalt salt and nickel salt; (2) Dissolve 10 mol of hexamethylenetetramine in 24 mL of deionized water and stir evenly to obtain an aqueous solution of hexamethylenetetramine; (3) 5.33 mL of a 10 mg / mL aqueous solution of graphene oxide was mixed with 10.67 mL of N,N-dimethylformamide, and ultrasonically stirred for 24 h to obtain a mixed solution containing graphene oxide and N,N-dimethylformamide after full dispersion; (4) The three solutions obtained in steps (1), (2) and (3) are fully mixed, and then the obtained mixed solution is transferred to a polytetrafluoroethylene-lined container and subjected to solvent thermal treatment at 95°C for 10 h to obtain a CoNiO2 / rGO hydrogel; (5) washing and soaking the CoNiO2 / rGO hydrogel obtained in step (4) for multiple times to remove impurities, and then freeze-drying at a temperature of -65°C for 24 hours to obtain CoNiO2 / rGO aerogel; (6) The CoNiO2 / rGO aerogel obtained in step (5) was calcined at 500°C for 3h to obtain the cobalt nickel oxide-doped graphene aerogel composite material of the present invention, which was recorded as CNG-4.

[0050] Example 5 (1) Add 8 mmol of cobalt nitrate hexahydrate and 2 mmol of nickel nitrate hexahydrate into 40 mL of ethanol and stir evenly until the mixture is completely dissolved to obtain an alcohol solution of cobalt salt and nickel salt; (2) Dissolve 10 mol of hexamethylenetetramine in 24 mL of deionized water and stir evenly to obtain an aqueous solution of hexamethylenetetramine; (3) 5.33 mL of a 10 mg / mL aqueous solution of graphene oxide was mixed with 10.67 mL of N,N-dimethylformamide, and ultrasonically stirred for 24 h to obtain a mixed solution containing graphene oxide and N,N-dimethylformamide after full dispersion; (4) the three solutions obtained in steps (1), (2) and (3) are fully mixed, and then the obtained mixed solution is transferred to a polytetrafluoroethylene-lined container, and subjected to solvent thermal treatment at 200°C for 10 hours to obtain a CoNiO2 / rGO hydrogel; (5) washing and soaking the CoNiO2 / rGO hydrogel obtained in step (4) for multiple times to remove impurities, and then freeze-drying at a temperature of -65°C for 24 hours to obtain CoNiO2 / rGO aerogel; (6) The CoNiO2 / rGO aerogel obtained in step (5) was calcined at 500°C for 3h to obtain the cobalt nickel oxide doped graphene aerogel composite material of the present invention, which was recorded as CNG-5.

[0051] Comparative Example 1: The synthesis method is basically the same as that of Example 1, except that the calcination process in step (6) is not performed. The obtained aerogel is recorded as D1.

[0052] Comparative Example 2: The synthesis method is basically the same as that of Example 1, except that the temperature during the calcination process in step (6) is 700°C, and the obtained product is recorded as D2.

[0053] Test Example 1 The scanning electron microscope (SEM) test of the samples CNG-1 to CNG-5 and D1 and D2 obtained in Examples 1-5 and Comparative Examples 1-2 was performed using a JEOL IT-800 field emission scanning electron microscope from JEOL Ltd. The results are shown in the attached figure. Figure 1 As shown in the figure, Figure 1 As shown in (a), it can be seen that the CoNiO2 / rGO aerogel presents a nanoflower structure formed by self-assembly of nanosheets; Figure 1 As shown in (b), the nanoflower structure of the material is not affected after high-temperature calcination of CoNiO2 / rGO aerogel in air. Instead, the obtained Co3O4 / NiO / rGO aerogel has porous and nanoflowers self-assembled from finer nanosheets. Therefore, the Co3O4 / NiO / rGO aerogel finally obtained by the method described in the present invention retains its own morphological and structural characteristics, has a larger specific surface area and more surface active sites, which is conducive to obtaining better gas-sensing performance.

[0054] The specific surface areas of samples CNG-1 to CNG-5 and D1 and D2 obtained in Examples 1-5 and Comparative Examples 1-2 were tested using an American specific surface area and micropore analyzer (ASAP 2020). The results are shown in Table 1: Table 1

[0055] As can be seen from Table 1, the Co3O4 / NiO / rGO aerogel prepared by the method of the present invention has a higher specific surface area, which is beneficial to the diffusion and contact of gas molecules and improves the sensitivity; the aerogel has a larger specific surface area than the uncalcined aerogel D1 and the aerogel D2 calcined at a higher temperature, indicating that while maintaining the nanoflower-like microstructure, a porous structure is also formed, which can expose more active sites and is beneficial to further improve the gas-sensing performance.

[0056] Test Example 2 The samples CNG-1 to CNG-5 and D1 and D2 obtained in Examples 1-5 and Comparative Examples 1-2 were used as gas-sensitive materials, and the gas sensors TR1-5 (corresponding to Examples 1-5) and DTR1 and DTR2 (corresponding to Comparative Examples 1-2) required for the gas-sensitive performance test were prepared by the following method: S1. The commercially available flat-plate Au electrode (with extended platinum wire) was cleaned and dried with deionized water and ethanol respectively. The electrode was provided with a test electrode and a heating electrode. The electrode heating temperature could be controlled by adjusting the input current. The upper surface of the electrode was Au, which was the test end, and the lower surface was Ru, which was the heating end. The overall dimensions of the flat-plate electrode were 1.5×1.5 mm. S2. Weigh a certain amount of the cobalt-nickel oxide-doped graphene aerogel composite material of the present invention as a gas-sensitive material, add deionized water so that the mass ratio of deionized water to the gas-sensitive material is 1:1, and then quickly grind for 5-10 minutes to form a uniform paste slurry; S3. The slurry obtained in step S2 is evenly applied on the flat Au electrode to form an electrode film and completely cover the Au electrode. The obtained electrode is then placed on an aging table and aged at 60° C. for 48 hours.

[0057] The gas sensors TR1-5 and DTR1-2 prepared by the above method were tested for gas sensing performance using the CGS-8 intelligent gas sensing analysis system and the DGD-V digital dynamic gas distribution system produced by Beijing Zhongju High-Tech Technology Co., Ltd. Unless otherwise specified, the test temperature of the following tests is 120°C.

[0058] In the gas sensing performance test of the present invention, the sensitivity S is defined as ∆R / R a , R a is the initial resistance of the gas sensor in argon, R g is the resistance value of the gas sensor in the gas to be measured, ∆R is the difference between the resistance of the gas sensor in argon and the resistance in the gas to be measured |R g -R a |.

[0059] The resistance response of gas sensor TR1 to H2, CH4 and CO2 was tested respectively. The results are shown in the attached figure. Figure 2-6 As shown. Figure 2-4 It can be seen that the aerogel composite material CNG-1 prepared in Example 1, as a gas-sensitive material, responds to H2, CH4 and CO2 with a gas concentration of 10-5000ppm, and the response value to H2 is significantly higher than that to CH4 and CO2. Figure 5 It can be seen that as the H2 concentration increases, the sensitivity of the gas sensor TR1 continues to increase; the sensitivity gradually tends to be flat when the H2 concentration is 200ppm; as the H2 concentration continues to increase, the sensitivity almost no longer increases, indicating that the full scale of the gas sensor TR1 can reach 500ppm. Figure 6 It can be seen that the sensitivity of the gas sensor TR1 to H2 gas can reach 37.6%, 52.1%, 79.9%, 86.8%, 89.7%, 91.2%, 92.4%, 92.6% and 93.6% respectively. The above results show that the cobalt nickel oxide doped graphene aerogel composite material of the present invention has high sensitivity and selectivity to H2 at an operating temperature of 120°C, with a full scale of 500ppm and a maximum H2 sensitivity of 93.6%.

[0060] The sensitivity of gas sensors TR1-5 and DTR1-2 to H2, CH4 and CO2 was tested when the gas concentration was 200ppm. The results are shown in Table 2: Table 2

[0061] It can be seen from Table 2 that when the cobalt-nickel oxide-doped graphene aerogel composite material of the present invention is used as a gas-sensitive material, the sensitivity to H2 is significantly higher than that to methane and carbon dioxide, indicating that it has high sensitivity and selectivity to H2; compared with DTR1 prepared from an uncalcined sample and DTR2 prepared from a sample calcined at a higher temperature, it has better gas sensitivity, indicating that the composite material of the present invention, as a gas-sensitive material, can better detect H2 released in thermal runaway of lithium batteries, which is beneficial to early monitoring and early warning, and reduces the risk of use.

[0062] Test the repeatability of the gas sensor TR1 to the H2 gas with a gas concentration of 100ppm. Figure 7 As shown, after TR1 was repeated three times in a row, the gas sensing performance hardly changed, indicating that the cobalt nickel oxide-doped graphene aerogel composite material of the present invention has good repetitive stability when used as a gas sensing material.

[0063] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A cobalt-nickel oxide-doped graphene aerogel composite material, characterized in that: The material contains cobalt oxide, nickel oxide and reduced graphene oxide, and is in the form of porous nanoflowers with a specific surface area of ​​80-100m 2 / g.

2. The cobalt-nickel oxide-doped graphene aerogel composite material according to claim 1, characterized in that: Relative to 100 parts by weight of the reduced graphene oxide, the content of the cobalt oxide is 25-50 parts by weight, and the content of the nickel oxide is 5-35 parts by weight.

3. The cobalt-nickel oxide-doped graphene aerogel composite material according to claim 1 or 2, characterized in that: The cobalt oxide is Co3O4, and the nickel oxide is NiO.

4. A method for preparing a cobalt-nickel oxide-doped graphene aerogel composite material, characterized in that: The method comprises the following steps: (1) mixing an alcohol solution of cobalt salt and nickel salt, an aqueous solution of hexamethylenetetramine, and a mixed solution containing graphene oxide and N,N-dimethylformamide, and then performing a solvent thermal treatment to obtain a hydrogel; (2) freeze-drying the hydrogel obtained in step (1), and calcining the obtained aerogel.

5. The method according to claim 4, characterized in that In the alcohol solution of the cobalt salt and the nickel salt, the concentration of the cobalt salt is 0.04-0.50 mol / L, and the concentration of the nickel salt is 0.02-0.20 mol / L.

6. The method according to claim 4 or 5, characterized in that: The cobalt salt is cobalt nitrate and / or cobalt chloride, and the nickel salt is at least one of nickel nitrate, nickel chloride or nickel sulfate.

7. The method according to any one of claims 4 to 6, characterized in that: In the hexamethylenetetramine aqueous solution, the concentration of hexamethylenetetramine is 0.2-0.6 mol / L.

8. The method according to any one of claims 4 to 7, characterized in that: In the mixed solution containing graphene oxide and N,N-dimethylformamide, the concentration of graphene oxide is 5-15 mg / mL, and the volume fraction of N,N-dimethylformamide is 50-75 vol%.

9. The method according to any one of claims 4 to 8, characterized in that: The conditions of the solvent thermal treatment include: temperature of 80-200° C. and time of 5-20 h.

10. The method according to any one of claims 4 to 9, characterized in that: The freeze-drying conditions include: temperature of -80°C to -55°C, and time of 18-36 hours.

11. The method according to any one of claims 4 to 10, characterized in that: The calcination conditions include: temperature of 400-600° C. and time of 1-6 hours.

12. A cobalt nickel oxide doped graphene aerogel composite material prepared by the method according to any one of claims 4 to 11.

13. Use of the cobalt nickel oxide doped graphene aerogel composite material as claimed in any one of claims 1 to 3 and 12 as a gas sensitive material of a gas sensor.

14. A gas sensor, characterized in that: The gas sensitive material of the gas sensor is the cobalt-nickel oxide-doped graphene aerogel composite material as described in any one of claims 1-3 and 12.